PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP AKTIVITAS BELAJAR PESERTA DIDIK PADA MATA PELAJARAN GEOGRAFI - Ardhy Muhamad Firman, - (2019)
The talking stick type cooperative learning model can develop learners' learning activities by involving visual activities, oral activities, listening activities and motor activities. The purpose of this research is to find out: (1) learning activities of students in the experimental class with the cooperative learning model of the talking stick type (2) the learning activities of the students in the control class without the cooperative learning model of the talking stick type (3) differences in the learning activities of the experimental class with control class. This research uses an experimental method with a post-test only control design. The research subjects were students of class XI IPS 1 as an experimental class with cooperative learning model talking stick type and class XI IPS 3 as a control class with cooperative learning model type spontaneous group discussion. The instruments used were tests and observations. The data analysis technique used K-S normality test, levene homogeneity test, and independent sample T-Test test. The results showed: (1) learning activities in the experimental class obtained an average percentage of 66% and 69% with high criteria (2) learning activities of students in the control class obtained an average percentage of 56% and 58% with moderate criteria (3 ) there are differences in learning activities between the experimental class and the control class as the results of the hypothesis test probability values are 0.002 and 0.000 <0.05, so Ha is accepted and Ho is rejected. In conclusion, the talking stick type cooperative learning model influences the learning activities of students seen in the visual, oral, listening and motoric aspects.